Chapter 11 What makes academia (un)safe Experiences, observations, and consequences of gender-based violence in different stages of individual researchers' careers - Pilinkaite Sotirovic, Vilana (Taylor & Francis, 2024)
This book presents a novel and insightful examination of gender-based violence, inviting readers to consider this topic from various perspectives. It encompasses various conceptual discussions and international regulations and trends, while concurrently emphasising the legal regulations and practices of select Central and Eastern European countries. Significantly underrepresented in legal scholarship, this region has been overlooked and subject to limited comprehensive analyses. The authors address different aspects of gender-based violence, also covering some areas that have received little attention in academic literature, such as gender-based violence in academia and cyberstalking. Furthermore, the book incorporates recent empirical studies, thereby endowing readers with valuable insights into the specific challenges encountered in the region. By contributing to current research on gender-based violence in Europe, this publication is an invaluable resource for researchers, students, policymakers, and general readers interested in gender-based violence and the fight against it in the Central and Eastern European region.